"Amai a Pátria" : o ensino da disciplina escolar educação moral e cívica no Atheneu Sergipense (década de 70 do século XX) - Santos, Patrícia Batista dos (2012)
The present study investigates the School Subject Morals and Patriotic Education in Atheneu Sergipense in the 70s of the twentieth century. This study is connected to the theories and methodologies of School Subjects History and from the perspective of Cultural History. For the construction of this work were used scholars as a: André Chervel (l990), Ivor Goodson (2001, 1998, 1990), Dominique Julia (2001) and Viñao Frago (2008); beyond readings from the following sources: Documents of National Commission of Morals and Patriotic, Laws of Education, Records Book, Textbooks and writing activities. The investigation of the subject Morals and Patriotic Education in Atheneu Sergipense revealed that his teaching was connected to exposure of contents and patriotic practice. The content passed through the presentation of the patriotism, knowledge of the Brazilian State, as well as the creation of morals habits and behaviors. The surveys were conducted: in the Library and Archive of Atheneu Sergipense, in the State Corporation of Education of Sergipe and Dom Luciano José Cabral Library.